Answer:
![g_(moon)=1.67 [m/s^(2) ]](https://img.qammunity.org/2021/formulas/physics/high-school/a7hm066qqavo284n4gzhow7tcfnkxn6q0k.png)
Step-by-step explanation:
The weight of some mass is defined as the product of mass by gravitational acceleration. In this way using the following formula we can find the weight.
![w =m*g\\](https://img.qammunity.org/2021/formulas/physics/high-school/o4mdrdle946z26n3jagg4h2jifchda7jlf.png)
where:
w = weight [N]
m = mass = 0.06 [kg]
g = gravity acceleration = 10 [N/kg]
Therefore:
![w=0.06*10\\w=0.6[N]](https://img.qammunity.org/2021/formulas/physics/high-school/ftwbqxcee967usv32uahbi4qger2o10z70.png)
By Hooke's law we know that the force in a spring can be calculated by means of the following expression.
![F=W\\F = k*x](https://img.qammunity.org/2021/formulas/physics/high-school/ce65iwbkszvm9jmejsa233a3aizrwqoe0c.png)
where:
k = spring constant [N/m]
x = deformed distance = 6 [cm] = 0.06 [m]
We can find the spring constant.
![k= F/x\\k=0.6/0.06\\k=10 [N/m]](https://img.qammunity.org/2021/formulas/physics/high-school/k7gtq38cepzrd4k7s5eigcxsirlfs3w7rx.png)
Since we use the same spring on the moon and the same mass, the constant of the spring does not change, the same goes for the mass.
![F_(moon)=k*0.01\\F = 10*0.01\\F=0.1[N]](https://img.qammunity.org/2021/formulas/physics/high-school/9yqf67y0tjyfshm7rkkdcdpfdcdxhy2rm2.png)
Since this force is equal to the weight, we can now determine the gravitational acceleration.
![F=m*g_(moon)\\g=F/m\\g = 0.1/0.06\\g_(moon) = 1.67[m/s^(2) ]](https://img.qammunity.org/2021/formulas/physics/high-school/urm4cff1xpkma1bnllff77910ewyjirq3b.png)